Farm Women: Some Contemporary Themes - Cooper, Barbara (Labour/Le Travailleur, 1989)
Abstract This report examines some of the persistent themes in the social science literature about farm women since the middle of this century. It is one researcher's attempt to deal with the wide variety of perspectives from which farm women have been studied and to suggest the usefulness of some of the material for future scholarship.